The Influence of Operating Cash Flows, Investments Cash Flow, and Funding Cash Flow on the Company Value in Technology Sector - Herman; Randy Chaidir (Ilomata International Journal of Tax and Accounting, 2023)
Investors use the company value as one of the benchmarks in investing the capital since the value is generated from the share price with the basis of the company performance and the public assessment on that performance. The company value can be measured by Price Earning Ratio (PER), Price Book Value (PBV), and Tobin's Q. Price Book Value is selected in this research as its measurement. The research subjects were technology-based companies listed in the Indonesian stock exchange. From the data obtained, it was indicated that there were fluctuations in the value of technology-based companies. This is a dilemma for both the companies and the investors on the grounds that not only the management but also the investors expect the company value to consistently increase. The research sample were 28 companies that met the criteria, within the periods of 2019-2022. The method used was quantitative research with multiple regression analysis as its analytical tool. The results indicated that the operating cash flow, the investment cash flow, and the financing cash flow have no effects on the firm value.